1977
DOI: 10.1007/bf00609864
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependent pharmacokinetics of prednisolone

Abstract: The pharmacokinetics of prednisolone elimination have been studied in both arthritic patients and normal volunteers using tritiated prednisolone alone, and in conjunction with unlabelled prednisolone in doses of 0.15 mg-kg-1 and 0.3 mg-kg-1 body weight. With increasing dose there is prolongation of the plasma half-life and increase in the volume of distribution and plasma clearance of prednisolone. It is proposed that these changes in pharmacokinetic parameters may be associated with non-linear binding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…One suggested cause of non-linear pharmacokinetics for prednisolone is saturation of plasma protein binding (Pickup et al, 1977 Tanner, Bochner, et al (1979) found a mean bioavailability of 98.5 + 4% which is consistent with our own observations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…One suggested cause of non-linear pharmacokinetics for prednisolone is saturation of plasma protein binding (Pickup et al, 1977 Tanner, Bochner, et al (1979) found a mean bioavailability of 98.5 + 4% which is consistent with our own observations.…”
Section: Discussionsupporting
confidence: 91%
“…Although linear regression of all their data showed the best correlation, they suggested that proportionality of AUC to dose was only operative over the range 5-20 mg and that above this dose a lesser increase in AUC than might be expected was produced by dosage increments. Pickup et al (1977) used an extrapolation method to estimate the apparent volume of distribution (from which they then calculated clearance). This assumes that prednisolone confers the properties of a single compartment model on the body following intravenous administration although their results (and ours) show this to be invalid.…”
Section: Discussionmentioning
confidence: 99%
“…[31], [44], [49] With increasing dose, the volume of distribution of prednisolone increases, due to a shift in a larger fraction of the body burden from the plasma compartment to other body tissues or to sites of greater metabolic activity. [44] The concentration-dependent binding of prednisolone to the plasma proteins (i.e., transcortin and albumin) results in the dose-dependent nonlinear pharmacokinetics observed for prednisolone.…”
Section: Distributionmentioning
confidence: 99%
“…The fraction bound is not constant and decreases in a nonlinear fashion with increasing concentrations: at low concentrations protein binding appears to be quite high (80%-90%), but declines at higher prednisolone levels to 60%-70%. [33], [44], [49], [50], [52] For plasma concentrations of up to 400 ng/mL an approximate linear function of fraction bound can be assumed, which switches over to a constant (lower) relation above 600 ng/mL, [44] reflecting the saturable binding of prednisolone to transcortin. Binding of prednisolone to plasma protein is independent of the route of administration.…”
Section: Distributionmentioning
confidence: 99%
See 1 more Smart Citation